Microtus transcaspicus Satunin 1905 - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Microtus transcaspicus Satunin, 1905. Izv. Kavkas. Mus., 2:57. TYPE LOCALITY: Turkmenistan, Kopet Dag Mtns, Chuli Valley, near Ashkhabad. DISTRIBUTION: S Turkmenistan, N Afghanistan, and N Iran. SYNONYMS: khorkoutensis. COMMENTS: Subgenus Microtus, arvalis species group sensu Zagorodnyuk (1990). Taxonomy reviewed by Gromov and Polyakov (1977), Corbet (1978c), Malygin (1978), Meier et al. (1981), and Meier (1983). Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 531, DOI: 10.5281/zenodo.7353098